Monitoring Mast Cell Populations in Waldenström’s Macroglobulinemia: A Xenotransplantation Study - Siskos, Nikistratos; Bekiari, Chryssa; Poutahidis, Theophilos; Chadras, Alexandros; S. Tsingotjidou, Anastasia (Journal of Hematology and Oncology Research, 2019)
Waldenström Macroglobulinemia (WM) is a B-cell lymphoproliferative disorder characterized mainly by uncontrolled accrual of M- immunoglobulin, secreted by malignant lymphoplasmatic cells. Mast cells interacting with malignant B-cells play an important role at the manifestation of the disease. Utilizing a previous xenotransplantation mouse model, this study evaluates long-term implant viability and quantifies distinct bone marrow mast cell populations along with their dynamics in non-WM and WM human bone implants. Non-WM bone implants were obtained from the femoral head of adult humans undergoing hip arthroplasty or hemiarthroplasty, whereas WM human bone implants originated from bone biopsies obtained from the posterior iliac crest of patients with active WM. All bone particles were implanted intramuscularly in twenty-four NOD/SCID mice. Following 3, 4 or 8 months postoperatively, xenografts were removed and studied using special histological techniques to identify mature and immature mast cells. Xenografts survived up to 8 months after implantation presenting normal cytoarchitecture (non-WM) or high-grade neoplastic infiltration and microresorption (WM bone biopsies). Statistical analysis of mast cell populations showed significant elevation regarding time progression and bone marrow microenvironment, thus suggesting the possible influence of malignant cells to the mast cell population in WM. This study presents the extended survival of intramuscular implantation of human adult bone xenografts into NOD/SCID mice and provides additional information on the interaction between mast cells and malignant B-cells.
Keywords: Waldenström Macroglobulinemia; mast cells; human adult bone; xenotransplantation; SCID mice